Facile Preparation of Self-Assembled Chitosan-Based POSS-CNTs-CS Composite as Highly Efficient Dye Absorbent for Wastewater Treatment - Zhao, Hongjie (ACS Omega, 2020)
[Image: see text] In this work, a new nanocomposite based on octa-amino polyhedral oligomeric silsesquioxanes (POSS), carbon nanotubes (CNTs), and chitosan (CS) was synthesized and used for wastewater treatment. The properties and morphologies of the prepared composite were analyzed by X-ray diffraction, scanning electron microscopy, transmission electron microscope, thermogravimetric, and atomic force microscopy. The results showed that POSS, CNTs, and CS formed a stable composite through intermolecular forces, and the modification of CS by POSS and CNTs improved its stability. In addition, the obtained composite showed good adsorption performance for the degradation of methyl orange and Congo red dyes. The pseudo-first-order model and pseudo-second-order model were used to analyze the adsorption data, and the results showed that the adsorption process conforms to the kinetic model. Moreover, the maximum adsorption capacity of the composite to methyl orange and Congo red reached 63.23 and 314.97 mg/g, respectively. This work provides new ideas for the preparation of self-assembled multi-composite and their potential applications in wastewater treatment.